The EU polycrisis and hard populism in East -Central Europe: From the Copenhagen dilemma to the Juncker paradox - Ágh Attila (Sciendo, 2017)
Analyses of populism in East -Central Europe (ECE) necessarily depart from the general crisis of representative democracy in the EU and describe the ECE as a specifi c regional case reflecting the failure of the catch -up process. The first part of this article adopts this “classical” approach and considers the backsliding of ECE democracy alongside the rise of populist identity politics in the global context. In the second part, I turn to the historical trajectory of ECE populism as a “nested” or two -level game in the EU context of ECE developments. The third part of this article outlines the main contradictions in this process that has led to what I call the Juncker paradox. To understand this paradox, we need to return to what the Commission noted in the early 2010s as the Copenhagen dilemma: aft er the EU accession of ECE states, the EU had no means to control rule -of -law violations and, in fact, supported autocratic populist ECE regimes through European transfers. This article explains the worsening of this situation in the late 2010s as the EU polycrisis caused Juncker’s Commission to focus on Core -based priorities and marginalise rule -of -law violations in ECE. This inaction and neglect have produced a special case of negative externalities - the Juncker paradox - that has largely been counterproductive and further strengthened anti -EU populism in all ECE countries, especially Hungary and Poland. Despite this situation, I conclude that Juncker’s 2017 State of the Union address should be a turning point in the EU’s policy towards ECE; in particular, it should promote a better understanding of the regional situation and more effective enforcement of the rule of law.